MELT COMPOSITION CONTROL OF ZR/HF FRACTIONATION IN MAGMATIC PROCESSES - Linnen R.L.; Keppler H. (My University, 2002)
Zircon (ZrSiO4) and hafnon (HfSiO4) solubilities in water-saturated granitic melts have been determined as a function of melt composition at 800° and 1035°C at 200 MPa. The solubilities of zircon and hafnon in metaluminous or peraluminous melts are orders of magnitude lower than in strongly peralkaline melt. Moreover, the molar ratio of zircon and hafnon solubility is a function of melt composition. Although the solubilities are nearly identical in peralkaline melts, zircon on a molar basis is up to five times more soluble than hafnon in peraluminous melts. Accordingly, calculated partition coefficients of Zr and Hf between zircon and melt are nearly equal for the peralkaline melts, whereas for metaluminous and peraluminous melts DHf/DZr for zircon is 0.5 to 0.2. Consequently, zircon fractionation will strongly decrease Zr/Hf in some granites, whereas it has little effect on the Zr/Hf ratio in alkaline melts or similar depolymerized melt compositions.The ratio of the molar solubilities of zircon and hafnon for a given melt composition, temperature, and pressure is proportional to the Hf/Zr activity coefficient ratio in the melt. The data imply that this ratio is nearly constant and probably close to unity for a wide range of peralkaline and similar depolymerized melts. However, it changes by a factor of two to five over a relatively small interval of melt compositions when a nearly fully polymerized melt structure is approached. For most ferromagnesian minerals in equilibrium with a depolymerized melt, DHf > DZr. Typical values of DHf/DZr range from 1.5 to 2.5 for clinopyroxene, amphibole, and titanite. Because of the change in the Hf/Zr activity ratio in the melt, the relative fractionation of Zr and Hf by these minerals will disappear or even be reversed when the melt composition approaches that of a metaluminous or peraluminous granite. It is thus not surprising that fractional crystallization of such granitic magmas leads to a decrease in Zr/Hf, whereas fractional crystallization of depolymerized melts tends to increase Zr/Hf. There is no need to invoke fluid metasomatism to explain these effects. Results demonstrate that for ions with identical charge and nearly identical radius, crystal chemistry does not alone determine relative compatibilities. Rather, the effect of changing activity coefficients in the melt may be comparable to or even larger than elastic strain effects in the crystal lattice.